The Application of Compost TKKS and Various Doses of Coumpound Fertilizer to Increase Nutrient N, P, and K Also The Growth of Palm Oil Seed (Elaeis guineensis Jacq.) on The Main Nursery in The Ultisol Soil - Bambang Sukron Wibowo; Hamidah Hanum; Fauzi Fauzi (Universitas Sumatera Utara, 2017)
This study was aimed to see the effect of the application of compost and various doses of inorganic compound fertilizers to increase soil nutrients and plant growth. This research conducted at the Faculty of Agriculture USU Greenhouse and Laboratory Research and Technology USU, Medan in altitude ± 25 m above sea level in May 2015 until December 2015.This research used non factorial completely randomized design with 6 treatments and 3 replication so that there are 18 experimental units. The composition of the treatment are: P0 = control; P1 = 100% Compound Fertilizer; P2 = Compost TKKS 600 grams; P3 = Compost TKKS 600 grams + 50% Compound Fertilizer; P4 = TKKS Compost Fertilizer 600 gram + 100%; P5 = TKKS Compost Fertilizer 600 gram + 150%. The data were processed using ANOVA and HSD test at 5%. The results showed the better influence of compost treatment in improving P-available, K-dd,root dry weight, pH, C- organic, Mg-dd, and leaf dry weight than the control treatment. The best increased nutrients and plants growth were in the compost treatment.